2021
DOI: 10.2147/jep.s259317
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Serotonergic Agents for the Treatment of Schizophrenia

Abstract: Schizophrenia remains one of the most chronic and highly disabling mental disorder. To date, the pathomechanism of schizophrenia is not fully understood and current treatments are characterized by some limitations. First- and second-generation antipsychotics have shown clinical efficacy in treating positive symptoms, while are poorly effective on both negative symptoms and cognitive deficits. Moreover, they can involve many metabolic and neurological side effects, leading to low therapeutic compliance. Many ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Second, the lack of a convincing association between LAI SGA plasma concentrations and direct/indirect parameters of clinical effectiveness can not only be explained by a non-linear relationship [34], but also by the fact that D2 receptor dysfunction represents only one of the mechanisms underlying SCZ [5]. In this sense, other biological factors might be more directly related to LAI SGA plasma concentrations and be concomitantly reliable biomarkers of clinical amelioration (e.g., Brain-Derived Neurotrophic Factor-BDNF or sex steroids plasma concentrations) [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the lack of a convincing association between LAI SGA plasma concentrations and direct/indirect parameters of clinical effectiveness can not only be explained by a non-linear relationship [34], but also by the fact that D2 receptor dysfunction represents only one of the mechanisms underlying SCZ [5]. In this sense, other biological factors might be more directly related to LAI SGA plasma concentrations and be concomitantly reliable biomarkers of clinical amelioration (e.g., Brain-Derived Neurotrophic Factor-BDNF or sex steroids plasma concentrations) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…While such antipsychotics have a robust efficacy against the positive symptoms of SCZ, they are considered poorly effective in treating negative symptoms [4]. Second-generation antipsychotics (SGAs) were introduced to address these unmet clinical needs, resulting to be equally effective or better than FGAs, particularly for negative, depressive and cognitive symptoms [5,6], and relapse prevention [7,8]. For these reasons, clinical practice guidelines recommend SGAs as first-line compounds to treat patients with SCZ, also for the reduced risk of extrapyramidal side effects generally associated with FGAs.…”
Section: Introductionmentioning
confidence: 99%
“…This compound has established the safety and efficacy in Phase 2 double-blind, multicenter RCT, showing improvement in total PANSS score compared to placebo. The Brilaroxazine (RP5063) was compared in various doses, including 15 mg, 30 mg, and 50 mg, along with aripiprazole 15 mg as a placebo in patients with acute symptoms of SCZ [ 11 ]. This study showed significant improvement in PANSS score with all the doses mentioned above [ 11 ].…”
Section: Novel Treatment Options For Schizophreniamentioning
confidence: 99%
“…The Brilaroxazine (RP5063) was compared in various doses, including 15 mg, 30 mg, and 50 mg, along with aripiprazole 15 mg as a placebo in patients with acute symptoms of SCZ [ 11 ]. This study showed significant improvement in PANSS score with all the doses mentioned above [ 11 ]. The improvement in symptoms with 15 mg of RP5063 was shown in 34% of patients, while 30 mg and 50 mg showed improvement in symptoms in 34% vs. 46%, respectively [ 11 ].…”
Section: Novel Treatment Options For Schizophreniamentioning
confidence: 99%
“…5,22,28,[45][46][47][48][49] It is also a dopamine D 1 receptor-dependent indirect modulator of glutamatergic α-amino-3hydroxy-5-methyl-4-isoxazolepropionic acid 52 and N-methyl-D -aspartate (NMDA) GluN 2B receptors. 5,19,24,53,54…”
Section: Introduction To the Compoundmentioning
confidence: 99%